Village Kiai Leadership in Internalizing Character Education Values within Rural Muslim Communities - Idris Ahmadi; Hefny Hefny (Education and Sociedad Journal, 2024)
This study aims to analyze the leadership role of village kiai as key actors in instilling character education values within rural communities. This research employed a qualitative method with a descriptive design using a phenomenological approach. Data were collected through in-depth interviews and direct observations to obtain comprehensive and relevant findings. The results reveal that village kiai function not only as religious leaders and educators but also as central figures and mediators in resolving social issues within the community. Their leadership is characterized by religious charisma, spiritual influence, democratic deliberation, and participatory approaches. The primary character values cultivated by village kiai include religiosity, honesty, discipline, independence, responsibility, and consistency in learning. The strategies implemented to instill these values involve habituation, role modeling, motivation, advice, storytelling, and disciplinary measures. Furthermore, the study identifies several challenges faced by village kiai, including deeply rooted cultural traditions, resistance to social change, difficulties in transforming community behavior, the growing influence of digital exposure, and limited governmental support. This study highlights the significant contribution of village kiai leadership to strengthening character education and social cohesion in rural Muslim communities.